Analysis of The Level of Understanding of Injury Handling in Female Football Athletes at STKIP Pasundan - Meyysi Ayu Ningrum; Gugun Gunawan; Indra Sholehudin (STKIP Pasundan Press, 2025)
This study aims to analyze the level of understanding of injury management among members of the Women's Football UKM at STKIP Pasundan. A quantitative approach with a descriptive survey design was used. Data were collected through a closed-ended questionnaire distributed to 20 active athletes. The results showed that respondents’ understanding was categorized as